A novel inhibitory domain of Helicobacter pylori protein CagA reduces CagA effects on host cell biology - Pelz, Christiane; Steininger, Sylvia; Weiss, Claudia; Coscia, Fabian; Vogelmann, Roger (The journal of biological chemistry, 2011)
The Helicobacter pylori protein CagA (cytotoxin-associated gene A) is associated with an increased risk for gastric cancer formation. After attachment to epithelial cells, the bacteria inject CagA via a type IV secretion apparatus into host cells, where it exerts its biological activity. Host cell responses to intracellular CagA have been linked exclusively to signaling motifs in the C terminus of the CagA protein. Little is known about the functional role of the remaining CagA protein. Using transgenic expression of CagA mutants in epithelial cells, we were able to identify a novel CagA inhibitory domain at the N terminus consisting of the first 200 amino acids. This domain localizes to cell-cell contacts and increases the rate and strength of cell-cell adhesion in epithelial cells. Thus, it compensates for the loss of cell-cell adhesion induced by the C terminus of the CagA protein. Consistent with its stabilizing role on cell-cell adhesion, the CagA N terminus domain reduces the CagA-induced β-catenin transcriptional activity in the nucleus. Furthermore, it inhibits apical surface constriction and cell elongations, host cell phenotypes induced by the C terminus in polarized epithelia. Therefore, our study suggests that CagA contains an intrinsic inhibitory domain that reduces host cell responses to CagA, which have been associated with the formation of cancer.